Opportunity Recognition Competence of women Entrepreneurs, and its effect on Performance of women owned enterprises in Uganda - Masiko, Murezi Caroline; Agaba Moses; Kikawa, Cliff Richard; Kaaya, Siraje (Husnayain Business Review, 2024)
In Uganda, women have found alternative forms of employment through entrepreneurship, though research indicates that males tend to dominate in the field of entrepreneurship. However, women can succeed in entrepreneurship if they have the right information, abilities, resources, and encouragement. This study sought to provide deeper insights on opportunity recognition as a competence that influences performance of female led/owned enterprises. It concentrates on women’s ability to recognize entrepreneurial opportunities, and how this impact on the performance of women owned/led enterprises. This study presented a conceptual model predicting the performance of women entrepreneurs, building on the body of literature already available in the fields of women entrepreneurship, and opportunity recognition of women entrepreneurs. The article concluded with significant theoretical and practical research implications and offers avenues for future research.